The theory of planned behavior : an evaluation methodology for employee assistance programs : a thesis presented in partial fulfilment of the requirements for the degree of Master of Business Studies in Human Resources Management at Massey University - Couturier, Marie Patricia (Massey University, 1999)
This study examines Ajzen's (1991) Theory of Planned Behavior (TPB) as a model that can be used to provide a theoretical foundation and sound methodology for the evaluation of Employee Assistance Programs (EAPs). Research in the field of EAPs has shown that employees' willingness to use the program is indicative of successful implementation (Hall, Vacc & Kissling, 1991; Harris & Fennell, 1988; Milne, Blum & Roman, 1994). The TPB proved to be extremely useful in gauging this willingness or intention to use the EAP in an organizational setting. A questionnaire was administered to 2,719 employees in a large health care setting with a response rate of 23%. The results showed 59% of the variance in the hierarchical multiple regression analysis was explained by the three components of the TPB, attitudes, subjective norms and perceived behavioral control. Furthermore, each of the components contributed to explaining the specific beliefs about EAPs held in this population. In particular, the beliefs that using an EAP provides help and that it can help improve work performance were significant to contributing to the attitudes held by this sample. In analyzing the results, it was evident that a reasonably successful implementation of the EAP had taken place in this organization. However, through the various components, it was possible to make an evaluation of the EAP and determine what areas can be changed or enhanced to increase the intentions. The conclusion was made that the TPB is a useful methodology to evaluate an EAP.
Keywords: New Zealand; Employee assistance programs -- Evaluation; Human behavior